Whole genome sequencing of Mycobacterium bovis directly from clinical tissue samples without culture - Zeineldin, Mohamed; Camp, Patrick; Farrell, David; Lehman, Kimberly; Thacker, Tyler (Frontiers in Microbiology, 2023)
Abstract Advancement in next generation sequencing offers the possibility of routine use of whole genome sequencing (WGS) for Mycobacterium bovis (M. bovis) genomes in clinical reference laboratories. To date, the M. bovis genome could only be sequenced if the mycobacteria were cultured from tissue. This requirement for culture has been due to the overwhelmingly large amount of host DNA present when DNA is prepared directly from a granuloma. To overcome this formidable hurdle, we evaluated the usefulness of an RNA-based targeted enrichment method to sequence M. bovis DNA directly from tissue samples without culture. Initial spiking experiments for method development were established by spiking DNA extracted from tissue samples with serially diluted M. bovis BCG DNA at the following concentration range: 0.1 ng/µl to 0.1 pg/µl (10-1 to 10-4). Library preparation, hybridization and enrichment was performed using SureSelect custom capture library RNA baits and the SureSelect XT HS2 target enrichment system for Illumina paired-end sequencing. The method validation was then assessed using direct WGS of M. bovis DNA extracted from tissue samples from naturally (n=6) and experimentally (n=6) infected animals with variable Ct values. Direct WGS of spiked DNA samples achieved 99.1 % mean genome coverage (mean depth of coverage: 108X) and 98.8 % mean genome coverage (mean depth of coverage: 26.4X) for tissue samples spiked with BCG DNA at 10-1 (mean Ct value: 20.3) and 10-2 (mean Ct value: 23.4), respectively. The M. bovis genome from the experimentally and naturally infected tissue samples was successfully sequenced with a mean genome coverage of 99.56% and depth of genome coverage ranging from 9.2X to 72.1X. The spoligoyping and M. bovis group assignment derived from sequencing DNA directly from the infected tissue samples matched that of the cultured isolates from the same sample. Our results show that direct sequencing of M. bovis DNA from tissue samples has the potential to provide accurate sequencing of M. bovis genomes significantly faster than WGS from cultures in research and diagnostic settings.